2021
DOI: 10.1038/s42004-021-00545-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of 3-ethyl-2,5-dimethylpyrazine by L-threonine 3-dehydrogenase and 2-amino-3-ketobutyrate CoA ligase/L-threonine aldolase

Abstract: Pyrazines are typically formed from amino acids and sugars in chemical reactions such as the Maillard reaction. In this study, we demonstrate that 3-ethyl-2,5-dimethylpyrazine can be produced from L-Thr by a simple bacterial operon. We conclude that EDMP is synthesized chemoenzymatically from L-Thr via the condensation reaction of two molecules of aminoacetone and one molecule of acetaldehyde. Aminoacetone is supplied by L-threonine 3-dehydrogenase using L-Thr as a substrate via 2-amino-3-ketobutyrate. Acetald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…When SDU70 was fed with 13 C-labeled S-adenosylmethionine (SAM), no isotopic coralinones were accumulated, excluding the possibility that 5-CH 3 is an outcome of putative C -methyltransferase. As Motoyama and co-workers have shown that aldehydes could participate in the alkylation of pyrazines, we conducted an additional isotope experiment using [1- 13 C]-labeled formaldehyde, but still no incorporation was observed in the LC-MS analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When SDU70 was fed with 13 C-labeled S-adenosylmethionine (SAM), no isotopic coralinones were accumulated, excluding the possibility that 5-CH 3 is an outcome of putative C -methyltransferase. As Motoyama and co-workers have shown that aldehydes could participate in the alkylation of pyrazines, we conducted an additional isotope experiment using [1- 13 C]-labeled formaldehyde, but still no incorporation was observed in the LC-MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As Motoyama and S1. co-workers have shown that aldehydes could participate in the alkylation of pyrazines, 22 we conducted an additional isotope experiment using [1-13 C]-labeled formaldehyde, but still no incorporation was observed in the LC-MS analysis. SDU70 was genome sequenced and then subjected to antiSMASH analysis, 23 which led to the identification of 44 biosynthetic gene clusters (BGCs).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Alk/AlkO-Pyrs are also used to improve the odor of cosmetics and toiletries in the perfume industry, , while AlkPyrs specifically have garnered interest and are supplied at ∼2200 kg/year as of 2004. , There are no recent reports available on the annual bulk supply of AlkPyrs; however, several new studies (from 2021) describe the effects of AlkPyrs related to food, chemical communication among insects, antimicrobial activity, their synthetic and biosynthetic formation, and organoleptic sensory notes. These recent AlkPyr highlights suggest a continued strong demand for pyrazine commodity chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…α-Aminoketones are prominent in the biosynthesis of a variety of important natural products. They are also a versatile and highly functionalizable motif in organic chemistry and are gaining increasing attention as valuable starting materials and intermediates for synthesis. Due to the difficulty of obtaining unprotected α-aminoketones synthetically, several biocatalytic routes toward this key synthetic building block have been explored . One method applied the popular pyridoxal 5′-phosphate (PLP)-dependent transaminases (TAs) to transfer an amino group from an amine donor to a diketone acceptor .…”
mentioning
confidence: 99%
“…The active site of Th AOS, showing the PLP cofactor bound to K243. The Th AOS structure (PDB: 7POA ) was aligned with the PLP- l -Thr PLP external aldimine complex of Cupriavidus necator KBL (PDB: 7BXQ , green) 2 and the S. paucimobilis SPT PLP- l -Ser external aldimine complex (PDB: 2W8J , pink). 17 …”
mentioning
confidence: 99%